Rise of the robots technology and the threat of a jobless future - Ford, Martin (Michigan Brilliance Audio, 2015)
In Silicon Valley the phrase "disruptive technology" is tossed around on a casual basis. No one doubts that technology has the power to devastate entire industries and upend various sectors of the job market. But Rise of the Robots asks a bigger question: Can accelerating technology disrupt our entire economic system to the point where a fundamental restructuring is required? Companies like Facebook and YouTube may only need a handful of employees to achieve enormous valuations, but what will be the fate of those of us not lucky or smart enough to have gotten into the great shift from human labor to computation?
Keywords: Labor supply--Effect of automation on